Alkaline activation of marble-like carbon structure and it's application for inflammatory adsorption. (July 2020) - Ulfa, Maria; Mangesti Gumilar, Ivara; Prasetyoko, Didik
Abstract: For the first time, carbon microspheres successfully synthesized by using block copolymer F127 combined with gelatin, sucrose, and H2 SO4 as soft template, source carbon, catalyst, respectively. The following step of synthesis are hydrothermal treatment, evaporation, carbonization and pyrolysis treatment under nitrogen flow. Microspheres carbon results have activated by a 10% KOH solution at room temperature for 12, 24, and 48 h, respectively then characterized by SEM and FTIR. The Activated microspheres carbon have used for ibuprofen adsorption. The characterization results showed that carbon microspheres carbon as marbles-like morphology with a diameter of 1-10 μm completed by C-OH, CO2, C≡N, -CNN, C=O, COO-, C=C, CK functional groups as the most. So this study shows that increasing activation time of the microsphere carbon have enhanced the equilibrium time and which is reach equilibrium at range 15-25 min and adsorption capacity range at 55.1-59.9 mg g −1 . So carbon microspheres in general conclusion could be potentially as Drug Delivery material.